2007
DOI: 10.1002/ps.1516
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of menthol derivatives against mosquitoes

Abstract: In ester derivatives of L-menthol the optimum activity is dependent on the size and shape of the ester group and the presence of chlorine atoms in the ester group. In structurally related derivatives of L-menthol the optimum activity is dependent on the aromaticity, the degree of unsaturation, the position of the hydroxy group and the type of functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 17 publications
1
51
1
2
Order By: Relevance
“…Lashgari et al (2014) melaporkan M. piperita memiliki efek fumigan yang menyebabkan kematian, serta memiliki aktifitas repelen terhadap imago T. castaneum. Senyawa mentol yang merupakan senyawa utama tanaman pepermin M. piperita memiliki efek repelen terhadap Anopheles tessellatus dan Culex quinquefasciatus (Samarasekera et al 2008).…”
Section: Pendahuluanunclassified
“…Lashgari et al (2014) melaporkan M. piperita memiliki efek fumigan yang menyebabkan kematian, serta memiliki aktifitas repelen terhadap imago T. castaneum. Senyawa mentol yang merupakan senyawa utama tanaman pepermin M. piperita memiliki efek repelen terhadap Anopheles tessellatus dan Culex quinquefasciatus (Samarasekera et al 2008).…”
Section: Pendahuluanunclassified
“…[13,[140][141][142][143] Menthol Cholesterol HMG-CoA reductase Inhibits the HMG-CoA reductase activity and reduce cholesterol in rodent models. [140][141][142]144] Perillyl alcohol Cancer Mannose-6-phosphate/ insulin-like growth factor II receptor Has a chemopreventive/therapeutic properties against, liver, mammary, cancer in Fisher 344 rats and human MIA PaCa-2 cells.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Menthol is a cyclic terpene alcohol that has been used as traditional herbal medicines and cooling agents in cosmetic products 5,6) . Menthol also shows various pharmacological activities including antimicrobial, antiinflammatory, analgesic, and central nervous system excitation effects [5][6][7][8][9][10] . Previous reports indicated that fatty acidascorbyl ester, conjugate of fatty acids and ascorbic acid, find attractive applications as an antioxidant in cosmetics, pharmaceuticals and food ingredients [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%